Cross-sectional study of the breastfeeding practices among women delivering in a tertiary care hospital in Puducherry, India - A., Kalaivani; D. Garg, Manasi; Srinivasa Rao, Majeti (International Journal of Contemporary Pediatrics, 2019)
Background: Global Public Health recommends that infants should receive only breastfeeding for first 6 months of life for their optimal growth and development. This study was done to find the rate of exclusive breast feeding and other feeding practices in children up to 6 months of age. Methods: A hospital based longitudinal study was conducted in a tertiary care hospital for a period of one year. Data from 158 mothers who were admitted for safe confinement was collected using structured questionnaire which was administered at every monthly follow up visit following delivery till first six months. Data included socio-demographic factors, psychosocial factors, breastfeeding details, maternal and infant factors. Data was entered in MS-Excel and analysed on SPSS version 18 software. Results: About 82.9% mothers had the knowledge about benefits of breastfeeding. Breastfeeding was initiated within one hour in 74% babies but exclusive breastfeeding for first six months was given only in 42.4% babies. Pre-lacteal feeds were given only in 3.2% babies. Early complementary feeds were started in 57.6% predominantly with cereal based diet. Perceived insufficiency of milk (30.3%) was the major reason mentioned for starting early complementary feeds. Conclusions: There is a wide gap between the knowledge and practice of exclusive breastfeeding. The importance of exclusive breastfeeding should be reinforced at every immunization visit so as to increase the rate of exclusive breastfeeding.